MULTICULTURALISM AND INTERCULTURALISM: REALITY OR VISION IN TEACHING - Birzniece, Baiba; Latsone, Lāsma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Today, the increasing mobility of people, globalisation and various political and economic circumstances have created a situation in which intercultural communication issues are more often on our minds. As shown on the Official Statistics website, of the 38708 long-term migrants who arrived in Latvia in 2022, only 5214 were ethnic Latvians, while 7758 were school-age children (Latvijas oficiālā statistika, 2023). The publication examines the experience of intercultural education in Latvia to date, keeping in mind that not only in Latvia, but also globally, there are different opinions on how much attention should be paid on intercultural education issues in schools. The aim of this publication is to analyse the readiness of general education teachers of Latvia to work in multicultural classrooms using the teaching methods, which require a pedagogical approach based on a tolerant attitude towards ethnic, cultural and religious differences between the people. The main research question: how much teachers in comprehensive schools are aware of intercultural education issues and willing to use intercultural education methods in their work. The study is based on the results of a survey of teachers working in grades 1-12 in general education schools. The research results lead to the conclusion that teachers’ awareness on intercultural issues is not sufficient.